Don’t cut your marketing budget in a recession - KUMAR, Nirmalya (Institutional Knowledge at Singapore Management University, 2020)
Most companies reduce spending in recessions, especially on marketing items that may be easier to cut (certainly relative to payroll). Right now, advertising agencies are struggling to stay afloat, and Google and Facebook are reporting substantially lower ad revenues as marketing spending dives with the business cycle (cyclical marketing). But that is today’s equivalent of bleeding – an old-fashioned but once widespread treatment that actually reduces the patient’s ability to fight disease. Companies that have bounced back most strongly from previous recessions usually did not cut their marketing spend, and in many cases actually increased it. But they did change what they were spending their marketing budget on and when to reflect the new context in which they operated.